Seasonal changes and determination of heavy metal concentrations in Veshaw river of the Indian western Himalaya - Rather, Rauoof Ahmad; Ara, Shoukat; Sharma, Sanjeev; Padder, Shahid Ahmad; Lone, Farooq Ahmad; Mir, Shakeel Ahmad; Baba, Zahoor Ahmad; Ayoub, Iqra Binti; Mir, Ikhlaq Ahmad; Bhat, Tariq Ahmad; Baba, Tawseef Rehman (Frontiers in Environmental Chemistry, 2022)
Trace elements are a major pollutant in the river water and these pollutants are present in all components of the ecological system. Since time immemorial, the River Veshaw has been one of the important sources of water and has shaped the cultural and social values in the Kashmir Valley. This study was conducted in rural parts of South Kashmir in the Western Himalaya from February to January 2020–2022. The river Veshaw provides various ecosystem services to the local communities as well as in the upper and lower stream regions in the form of many direct and indirect ecosystem services. The river is polluted by human waste from both rural and urban communities, as well as by agricultural runoff and effluent discharges from a variety of industrial activities due to its proximity. Effluent that makes it to the river contains a variety of pollutants, some of which are trace elements that accumulate in the local ecosystem, killing off plants and animals and reducing biodiversity. Trace element levels in water and sediment were found to follow the trend as: Sangam > Khudwani > Kulgam > Nihama > Aharbal > Kingwattan. The dominance pattern of heavy metals in water was Pb > As > Cd. The overall trend showed a downward trend of heavy metals, indicating the effect of land area drainage and anthropogenic activities on the stream water. The dominance pattern of heavy metals in water was Pb > As > Cd. Heavy metals were not detected in the middle and upstream sites. The average levels of heavy metals were highest at Downstream (Sangam), with values of Cd, Pd ad As 0.0054, 0.038 and 0.038 mgL-1. This shows that land drainage and human activities have an effect on the water in the stream.